2006
DOI: 10.1111/j.1463-1318.2006.01088.x
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal three‐dimensional endosonography and anal manometry in assessing anterior rectocele in women: a new pathogenesis concept and the basic surgical principle

Abstract: Obstetric trauma does not seem to play any role in rectocele pathogenesis because the anal sphincter muscles are anatomically and functionally normal and rectocele is also present in nuliparous and in women with caesarian sections. It seems that it is associated with the absence of EAS and thinner IAS in the anterior upper anal canal. Herniation starts at the upper anal canal extending to the lower rectum in high or large rectoceles and maybe produced by rectal intussusception because of excessive and prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
1
18
1
Order By: Relevance
“…The shorter anterior EAS and IAS in females produces a longer gap with a low-resistance upper anal canal wall, predisposing to fecal incontinence due to vaginal deliveries or proctologic procedures, especially in older women with neurogenic disturbances [9]. We recently demonstrated that rec- tocele is formed at the upper anal canal wall, extending to the lower rectum only in large herniations [11]. In conclusion, 3-D anal endosonography has enabled the measurement of the various anatomical structures of the anal canal and demonstrated accurately its asymmetrical configuration.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The shorter anterior EAS and IAS in females produces a longer gap with a low-resistance upper anal canal wall, predisposing to fecal incontinence due to vaginal deliveries or proctologic procedures, especially in older women with neurogenic disturbances [9]. We recently demonstrated that rec- tocele is formed at the upper anal canal wall, extending to the lower rectum only in large herniations [11]. In conclusion, 3-D anal endosonography has enabled the measurement of the various anatomical structures of the anal canal and demonstrated accurately its asymmetrical configuration.…”
Section: Discussionmentioning
confidence: 98%
“…Some reports have demonstrated that the anterior external anal sphincter (EAS) length varied according to gender (being shorter in women) using bidimensional images with 3-D reconstruction [6][7][8][9]. Using the new endoprobes with automatic scanning, the complex anal canal anatomy has been better analyzed in multiplanar imaging and the anal sphincter length and thickness have been precisely identified and measured [10][11][12][13].…”
mentioning
confidence: 99%
“…This means that other factors attributing to the formation of rectoceles must be taken into account, like excessive stressing during defecation or inherent anatomical disorders in the anal canal. For example, Redagas et al indicted that the presence of rectocele can be caused by the absence of external anal sphincter and by the thinning of internal sphincter in the upper anal canal [34].…”
Section: Discussionmentioning
confidence: 99%
“…The median height of the surgical specimen of 5.6 cm (range 4.5-10 cm) and the surface area removed (average 45 cm 2 ) by the TST STARR PLUS compare favorably with that of two firings of the PPH (average 37 cm 2 ) or the multiple firings of the Transtar (average 54 cm 2 ). The median height of the tissue removed using the EEA 33 is 5.9 cm (range 5-7.5 cm) which is comparable to that removed with the TST STARR PLUS [4].…”
mentioning
confidence: 71%
“…In patients with rectocele, the resection must be close to the dentate line (approximately 1.0 cm proximally) because the herniation starts at the anterior upper anal canal, as suggested by echodefecography [4], and consequently the herniation will persist if the stapled suture is positioned far above that level. Therefore, in female patients with rectocele associated with rectal intussusception, we have proposed the transanal repair of rectocele and rectal mucosectomy with one circular stapler (TRREMS) which may be performed with either the EEA-33 or TST STARR PLUS stapler [5].…”
mentioning
confidence: 99%